Prinsip Arsitektur Berkelanjutan sebagai Basis Membangun Kemandirian Obyek Cagar Budaya Pesanggrahan Langenharjo Kabupaten Sukoharjo - Triratma, Bambang (Universitas Sebelas Maret Surakarta, 2021)
Pesanggrahan Langenharjo is the Heritage building that was built by Sri Susuhunan Paku Buwono X, The King of Keraton Kasunanan Surakarta Hadiningrat 1893-1939. Those building was a place where the king and his family held some activities such as a family gathering, recreation and meditation, it has a spasific location at the river side of Sungai Bengawan Solo. Most of building has suffered various serious damages because of lack of maintenance. National and local Government doesn’t have a sufficient fund for carrying out a regular reparation and recovery to those degradation processes. This research aimed to build a self capabiity for conserving Pesanggrahan Langenharjo by creating a synergic interaction with some potential factors surrounding it. Some essences of the Sustaiable Architecture were applied in formulating the concept of the Grand Design for Pesanggrahan Langenharjo for empowering the self capability in carrying out its conservation. ‘A Litle Forrest of Pesanggrahan Langenharjo’ is a grand concept which accommodate the needs of conserving a historical value of building and maintening a natural resources simultaneously. Some various activities are going to be able to be held within the area together harmoniously in order to strengthen sustainability and durability of the building and its environmrnt.